Mapping and prediction of archaeological sites of habitation by modern humans using GIS and expert mapping on the south coast of South Africa - Kleyn, Philippa May (Rhodes University, Faculty of Science, Department of Geography, 2015)
South Africa contains many archaeological resources including shell middens from the Middle Stone Age (MSA) and Later Stone Age (LSA). These shell middens give researchers insight into the behaviour of modern humans where the first fossil evidence appears in Africa around 200 000 years ago (Klein, 2008). Research into shell middens is therefore vital to understand the origin of human kind. This study investigates whether Geographical Information Systems (GIS) is a useful tool for predicting locations of unknown shell midden sites using the characteristics of known areas of modern human habitation. This was done using suitability analysis and expert mapping techniques. Ground truthing of the results of the desktop analysis revealed that GIS is not a useful tool for predicting sites of modern habitation as the characteristics that determine human habitation are too variable.
Keywords: Geographic information systems -- South Africa; Archaeological sites; Kitchen-middens -- South Africa; Prehistoric peoples -- South Africa; Prehistoric peoples -- Dwellings -- South Africa; Geological mapping -- South Africa; Coastal archaeology -- South Africa; Archaeological significance -- South Africa